Exposure behaviour to Escherichia coli among households in Imvepi refugee settlement, Terego district Uganda - Aisha Nalugya; John C. Ssempebwa; James Muleme; Solomon T. Wafula; Bridget Nagawa Tamale; Arnold Tigaiza; Doreen Nakalembe; Winnifred K. Kansiime; John Bosco Isunju; Tonny Ssekamatte; Richard K. Mugambe (BMC, 2024)
Abstract Introduction Exposure to Escherichia coli (E. coli) is a risk factor for diarrhoeal diseases, which pose a significant problem in refugee settlements. Refugee populations are exposed to faecal microorganisms through multiple pathways including sub-optimal sanitary facilities, contaminated drinking water, produce and food, flood water, bathing water, and soil among others. While these pathways are well-documented, specific exposure behaviours remain underexplored. We assessed exposure behaviour to E. coli among households in Imvepi refugee settlement, Uganda, and provided evidence-based recommendations for the design of interventions to reduce excreta-related disease in refugee settlements. Methods Guided by the Sanitation Safety Planning approach, we surveyed 426 households in Imvepi refugee settlement, Uganda, using a digitized questionnaire and an observation checklist. We collected data on the background characteristics and exposure behaviour of women and emancipated girls (minors living on their own, having borne a child, married, or pregnant). The outcome variable, E. coli exposure behaviour, was measured using a five-point Likert scale, assessing behaviours that increase the risk of exposure. Data were cleaned in Microsoft Excel and analyzed in Stata version 17. Descriptive statistics were performed to summarize the data. We used modified Poisson regression to determine the factors associated with the outcome. Results Over 59.4% (253) exhibited high-risk exposure behaviour. Residing in compound homes (Adjusted Prevalence Ratio (APR) = 0.72, 95% Confidence interval (CI): 0.58-0.90), being aged 35-49 years (APR = 0.76, 95% CI: 0.60-0.97), having household heads with post-primary education (APR = 0.54, 95% CI: 0.38-0.77), high knowledge (APR = 0.69, 95% CI: 0.59-0.80), and high-risk perceptions regarding exposure to E. coli (APR = 0.75, 95% CI: 0.64-0.88) were associated with a lower prevalence of high-risk E. coli exposure behaviours. Conversely, having sanitary facilities with excreta overflowing from the squat hole (APR = 1.26, 95% CI: 1.08-1.48) was associated with a higher prevalence of high-risk exposure behaviours. Conclusion The study indicates a substantial prevalence of high-risk E. coli exposure behaviours in the refugee settlement.. There's a need to implement behaviour change interventions targeted at preventing or minimizing exposure, especially among households whose heads have low education attainment, those with young caretakers and those with limited knowledge and low-risk perceptions regarding exposure to E. coli.